Polemics and patronage in the city of victory: Vyāsatīrtha, Hindu sectarianism, and the sixteenth-century Vijayanagara Court - Stoker, Valerie (South Asia across the disciplines, 2016)
"How did the patronage activities of the Vijayanagara Empire (c. 1346-1565) influence Hindu sectarian identities? Contrary to most portraits of the empire as a Hindu bulwark against Islamic incursion from the north or as a religiously ecumenical state, in Polemics and Patronage in the City of Victory, Valerie Stoker argues that the Vijayanagara court was selective in its patronage of religious institutions. But the motivations behind this selectivity were not always religious. To understand the dynamic interaction between religious and royal institutions in this period, she focuses on the career of the Hindu intellectual and monastic leader Vyāsatīrtha. An agent of the state and a powerful religious authority, Vyāsatīrtha played an important role in expanding the empire's economic and social networks. By examining Vyāsatīrtha's polemics against rival sects in the context of his work for the empire, Stoker provides a remarkably nuanced picture of the relationship between religious identity and socio-political reality under Vijayanagara rule"--Provided by publisher.